Tanggung Jawab Rumah Sakit Atas Malpraktek pada Bidang Orthopedy yang dilakukan oleh Dokter pada saat Tindakan Operasi - Heri Subroto (Majelis: Jurnal Hukum Indonesia, 2024)
Malpractice is basically an action by professional staff that is contrary to the Standard Operating Procedure (SOP), professional code of ethics, and applicable laws, whether intentional or due to negligence. This negligence is not a violation of the law, if the negligence does not cause harm to other people and that person can feel comfortable. However, if this negligence results in material loss, harm or even takes the life of another person, then this can be said to be malpractice. Malpractice in the field of orthopedics is an act of negligence committed by doctors or health service workers who are tasked with carrying out all kinds of surgical procedures, especially bone surgery. Where in this case the patient who initially only experienced problems with his bones ultimately had to hamper his breathing for the last time just because of an error in administering gas after surgery. This fatal negligence can be said to occur due to a lack of accuracy on the part of doctors or other health workers in providing health services to patients. This negligence can also be caused by hospital management that is not well organized, the staff's education may still be minimal and many other factors. Because this action not only violates the law, the medical code of ethics and also the standards of behavior in a religion but even takes someone's life, there needs to be a way out, namely by; improving hospital management, increasing accuracy in carrying out the medical profession and deepening all kinds of knowledge about various kinds of health service procedures.